The role of D-serine as co-agonist of NMDA receptors in the nucleus accumbens: relevance to cocaine addiction - D’Ascenzo, Marcello; Podda, Maria Vittoria; Grassi, Claudio (Frontiers in Synaptic Neuroscience, 2014)
Cocaine addiction is characterized by compulsive drug use despite adverse consequences and high rate of relapse during periods of abstinence. Increasing consensus suggests that addiction to drugs of abuse usurps learning and memory mechanisms normally related to natural rewards, ultimately producing long-lasting neuroadaptations in the mesocorticolimbic system. This system, formed in part by the ventral tegmental area and nucleus accumbens (NAc), has a central role in the development and expression of addictive behaviors. In addition to a broad spectrum of changes that affect morphology and function of NAc excitatory circuits in cocaine–treated animals, impaired N-methyl-D-aspartate receptor (NMDAR)-dependent synaptic plasticity is a typical feature. D-serine, a D-amino acid that has been found at high levels in mammalian brain, binds with high affinity the co-agonist site of NMDAR and mediates, along with glutamate, several important processes including synaptic plasticity. Here we review recent literature focusing on cocaine-induced impairment in synaptic plasticity mechanisms in the NAc and on the fundamental role of D-serine as co-agonist of NMDAR in functional and dysfunctional synaptic plasticity within this nucleus. The emerging picture is that reduced D-serine levels play a crucial role in synaptic plasticity relevant to cocaine addiction. This finding opens new perspectives for therapeutic approaches to treat this addictive state.